Clinical characteristics and prognostic factors of sinonasal undifferentiated carcinoma: a multicenter study. Issue 9 (23rd June 2018) - de Bonnecaze, Guillaume; Verillaud, Benjamin; Chaltiel, Leonor; Fierens, Sylvestre; Chapelier, Mark; Rumeau, Cécile; Malard, Olivier; Gavid, Marie; Dufour, Xavier; Righini, Christian; Uro‐coste, Emmanuelle; Rives, Michel; et al.
Abstract : Background: Sinonasal undifferentiated carcinoma (SNUC) is a very rare entity with a poor prognosis. Due to the lack of studies on the subject, evidence is lacking concerning its management. Methods: A multicenter collaborative study was conducted to assess treatment strategy, oncological outcome, and prognostic factors. Results: Definitive analyses focused on 54 patients with a majority of advanced stage; the 3‐year overall survival (OS) and 3‐year recurrence‐free survival (RFS) rates were, respectively, 62.4% and 47.8%. During the follow‐up, 18 patients (33.3%) died, 10 (18.5%) developed metastases, 7 had lymph‐node involvement (13%), and 12 (22.2%) showed recurrence or local progression. In univariate analyses, treatment modalities associated with improved RFS were induction chemotherapy ( p = 0.02) and intensity‐modulated radiotherapy ( p = 0.007). In the multivariate analyses, only induction chemotherapy ( p = 0.047, hazard ratio [HR] = 0.39) was significantly associated with improved RFS. Conclusion: Multimodal therapies including induction chemotherapy and intensity‐modulated radiotherapy may improve the prognosis of SNUC; surgery might improve local control. Further multicenter studies are required.